Selecting the optimal scenario for the simultaneous application of diamond wire cutting and chainsaw machines in dimensional stone mines using SECA multi-criteria decision-making method (Rudarsko-geološko-naftni zbornik, 2025)
Currently, diamond wire cutting is used in most dimensional stone mines to extract stone blocks. Despite the capabilities of diamond wire cutting, stone extraction is associated with limitations or productivity loss in some cases. For this purpose, different scenarios resulting from the combination of diamond wire cutting and chainsaw machines had been investigated by discrete-event simulation in this research with the aim of improving the productivity of mining operations, and the best scenario was selected using the multi-criteria decision-making method of Simultaneous Evaluation of Criteria and Alternatives (SECA). In this research, the Shayan dimensional stone mine was selected as a case study, and based on the information related to mining operations, ten scenarios were defined for cutting the stone blocks. In the first scenario, a diamond wire cutting was alone used to cut all three sides of the block. In the second scenario, in addition to the diamond wire cutting, a chainsaw machine was added to the mining process to cut the back face of the block. In the third to sixth scenarios, in addition to the diamond wire cutting to cut side faces, a chainsaw machine was added to the mining process to cut the bottom face of the block. Depending on the continuity and intactness of the rock mass, and the need for horizontal drilling, the block dimensions varied across these scenarios. In the seventh to ninth scenarios, in addition to the diamond wire cutting to cut side faces, two chainsaw machines were used to cut both the back and the bottom faces of the block. These scenarios may differ in terms of the stone’s intactness, the need for horizontal drilling, and block dimensions. Finally, in the tenth scenario, both the back and bottom faces were cut using two chainsaw machines, while the side faces were cut using two squaring chainsaw machines. In order to find the best scenario to achieve the optimal technical and economic conditions, the SECA decision-making method was used due to the presence of several influential criteria. Based on the available information, four criteria including the production rate, capital cost, operating costs, and productivity were considered to compare the defined scenarios. According to the results, the final weights of the criteria were respectively equal to 0.228, 0.32, 0.239, and 0.213. Based on the criteria weights and the performance of each scenario across the criteria, the final scores of the scenarios were determined, and ultimately, the second scenario with a score of 0.655 emerged as the optimal configuration for the Shayan mine due to its balanced performance across all criteria.